Advantages and Necessity of Implementing Quality Assurance Management Systems (HACCP) in Food Processing Centers and Factories - Salari, Amir; Banori, َAttaulhaq (Journal of Natural Sciences – Kabul University, 2024)
In today’s world, the implementation of quality assurance management systems in food processing is recognized as a fundamental necessity in various societies. The diversity and wide range of food items require the establishment of advanced global quality management systems, such as HACCP, across all relevant stages to ensure comprehensive quality assurance. Providing and distributing safe and nutritious food to preserve public health is a primary goal of global organizations like ISO, WHO, and FDA, which have made extensive efforts over the past decade to develop and expand related documents and protocols. In food processing factories where a significant volume of food preparation and cooking occurs, utilizing modern control systems to reduce existing risks is essential. This article emphasizes the importance of safety and integrated management while examining the process of implementing the HACCP quality management system and its advantages from various perspectives in food processing centers and factories. HACCP is a comprehensive approach employed in the food industry to evaluate and control processes, focusing on identifying and preventing microbiological, physical, and chemical hazards that may occur at any stage of the food supply chain, production, or storage. Developing these policies in different societies can elevate production standards and address challenges related to food exportation. These standards are highly comprehensive and are currently accepted and required by relevant organizations and countries worldwide.